Decision regret and long-term weight evolution following laparoscopic sleeve gastrectomy as bridge to kidney transplantation - Yang, Xin Yu; Brazeau-Porrello, Pamela; Hajjar, Roy; Badrudin, David; Pescarus, Radu; Chan, Gabriel (Frontiers in Transplantation, 2025)
IntroductionLaparoscopic sleeve gastrectomy (LSG) is effective for rapid weight loss in kidney transplant (KT) candidates. This study aims to evaluate satisfaction or regret with the decision to undergo LSG in preparation for KT and the long-term durability of this approach to weight loss.MethodsFrom 2012 to 2019, all patients who underwent LSG prior to waitlisting for KT were included. The Decision Regret Scale (DRS) was assessed regarding the decision to undergo LSG before KT. The long-term weight evolution was also collected.FindingsForty-six subjects completed the DRS survey at a median follow-up of 8 years post-LSG: 67% reported absolutely no regret, 22% mild regret, and 11% moderate to strong regret. Successful surgical weight loss was achieved in 36 patients and was significantly associated with lower levels of regret (p = 0.005). Body mass index reductions after LSG were highly significant compared to baseline values at all time points over 10 years (p = 0.0001) and remained significantly lower for up to 7 years post-KT. Thirty-two patients received KT, yet this had no significant association with decision regret.ConclusionLaparoscopic sleeve gastrectomy as a pre-transplantation weight loss strategy is associated with very low levels of regret, regardless of the KT status. LSG has demonstrated long-term, durable weight loss.